HEPATOPROTECTIVE, ANTIDIABETIC, AND ANTIPYRETIC ACTIVITY STUDIES OF SIDDHA FORMULATION – NILAVEMBU KUDINEER - N, KASIRAJAN; B, MAHESHWARI; G, SUBASHCHANDRAN; KS, MAANICKHA CHELVI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Traditional medicines like Siddha System of Medicine are one of the most primitive medical system. It plays a major role in treating ailments of humankind. Nowadays, this system flourished throughout India using Nilavembu kudineer (NVK) as a drug to treat in various outbreaks such as dengue, Chikungunya, and other related virus infections. As per literature, NVK indicated many types of fever and various diseases. This study emphasizes on antipyretic, antidiabetic, and hepato protective activities of NVK by In vitro study methods. Methods: Hepatoprotective effect of NVK on Carbon tetrachloride-induced hepatotoxicity in the rat in five groups, antipyretic activity tested by subcutaneous injection of 10 ml/kg of 15% w/v yeast suspended in 0.5% w/v carboxymethyl cellulose solution for elevation of body temperature of rats in 6 groups. Antidiabetic activity done by administration of streptozotocin dissolved in citrate buffer (pH 4.5) and nicotinamide, intraperitoneal injection of 60 mg/kg streptozotocin, 15 min after the i.p administration of 120 mg/kg of nicotinamide in non-insulin-dependent diabetes, in six groups. Results: The hepatoprotective effect having the significance of one way ANOVA followed by Dunnett’s (n=6); nsp>0.05, *p<0.05, **p<0.01, and ***p<0.001, calculated by comparing treated groups tumor with the control group. Antidiabetic activity having the significance of Dunnett’s ***p<0.001, **p<0.01, and *p<0.05 calculated by comparing the treated group with the control group and antipyretic activity results in Dunnett’s *p<0.05 calculated by comparing the treated group with the control group were considered to be significant. Conclusion: The study shows that NVK having the potency of hepatoprotective and capability of diabetes in vitro studies. This study also revealed the potency of antipyretic activity against yeast.